RELATIONSHIP BETWEEN BIG FIVE PERSONALITY TRAITS AND PERCEIVED PARENTAL ATTACHMENT IN UNDERGRADUATE STUDENTS - Hanya Inam; Aisha Ateeq; Nazia Asif Takkhar; Dr Saima Majeed (Policy Research Journal, 2025)
The study had a cross-sectional design of quantitative nature to understand the relationship between perceived parental attachment and personality traits, the predictive power of perceived parental attachment and gender differences in both. A sample of 300 participants: 155 men and 145 women, aged 18-25 participated in the study. The sampling was purposive and conducted at public and private universities of Lahore. An information sheet, consent form, followed by Big Five Inventory, Parental Bonding Instrument, along with a demographic sheet were used. Ethical considerations were taken into account. The results were analyzed through SPSS version 26. The applied analysis was Pearson Product Moment Correlation, Multivariate Analysis of Variances and Multiple Linear Regression. The results showed significant positive relationship between perceived maternal care with agreeableness, conscientiousness, openness and a negative correlation between neuroticism. Moreover, there was a negative correlation between perceived maternal overprotection with agreeableness and conscientiousness. There was a negative correlation between paternal overprotection with agreeableness and a positive correlation with neuroticism. However, there were no significant relationships between extraversion and parental attachment. In addition, maternal care predicted openness. Moreover, maternal care, paternal care, and maternal overprotection predicted neuroticism. Maternal overprotection also predicted conscientiousness. The results from MANOVA indicated that women report a higher level of care, overprotection from their fathers than men, and a higher level neuroticism and openness than men. These results can help understand parental attachment and its effects onto personality. These findings can be incorporated into interventions during therapeutic modalities to better understand the roots of personality.